From an aging person to an elegant senior: a humanistic approach to viewing older adults - Cheng Fung-Kei (Sciendo, 2020)
The continuing growth in the number of adults aged 60-plus has raised global alertness of population restructuring. This demographic change, on the one hand, reduces productivity and increases public expenditure due to aging, resulting in prejudice, bias, misrepresentation, and discrimination against them. On the other hand, it develops a specific consumer market segment and extends the availability and accessibility of the elderly through employment, volunteering, or grandparenting. This study argues against the stigmatization of this age group from a functional perspective that damages social cohesion. It advocates a humanistic view toward seniors to eradicate marginalization and promotes the manageability of the senior population. With the aid of advanced technology and health equity, senior adults can retain everyday competence for self-care with dignity, as well as gracefully attain physical and psychological health, autonomy, and well-being in their later life. All these considerations give medical and nursing professionals insight into how to take care of the elderly.